Development and preliminary psychometric evaluation of an owner-completed measure of feline quality of life. (October 2017) - Tatlock, Sophi; Gober, Margaret; Williamson, Nicola; Arbuckle, Rob
Highlights: Health-related quality of life (HRQoL) is increasingly studied in companion animals but less so in cats. Forty-five pet owners completed an online survey confirming feline behavioural concepts from the literature. A 23-item feline QoL measure was drafted, capturing the identified concepts, and tested in qualitative pet owner interviews with pet owners. The measure was reduced to 22 items following qualitative pet owner interviews with pet owners, since items overlapped or were not relevant to pet-owners. The final measure demonstrated strong content and psychometric validity and reliability in a sample of healthy cats in the USA. Abstract: Due to improved healthcare and pet longevity, measurement of health-related quality of life (HRQoL) is increasingly important in companion animal medicine. The aim of this study was to develop and evaluate the content and psychometric properties of an owner-completed assessment of health and quality of life (QoL) in cats for use in general veterinary clinical practice. A 23-item feline QoL measure, drafted based on findings from an online survey completed by 45 pet owners, was revised following qualitative interviews with 10 pet owners of healthy cats to assess content validity. The resulting 22-item measure was completed twice by 199 owners of healthy cats to assess the reliability and validity of the measure via psychometric evaluation, including assessment of missing data, item response distributions, item correlations, factor analysis, internal consistency, test–retest reliability, multi-trait analysis, known groups analyses and estimation of minimally important differences. There were no missing data. Responses for all items were heavily skewed due to the sample being healthy. Analysis of items and factor analysis supported deletion of six items and calculation of two domain scores and a total score. Internal consistency and test–retest reliability were strong for all domains (0.70–0.80), indicating good reliability. All but three items demonstrated strong item convergent validity (item-scale correlation > 0.40) and correlated highest with their respective domain (item discriminant validity). Significant between-group differences in scores differing according to a global impression of feline health item provided evidence of discriminative validity. Findings provide evidence that the final 16-item feline QoL measure has strong cross-sectional psychometric properties.